A Q-ANALOGUE OF THE MULTIPLICATIVE CALCULUS: Q-MULTIPLICATIVE CALCULUS - Yener, Gokhan; Emiroglu, Ibrahim (AMER INST MATHEMATICAL SCIENCES, 2015)
In this paper, we propose q-analog of some basic concepts of multiplicative calculus and we called it as q-multiplicative calculus. We successfully introduced q-multiplicative calculus and some basic theorems about derivatives, integrals and infinite products are proved within this calculus.
Keywords: q-Calculus; q-analogues; multiplicative calculus; non-Newtonian calculus; Mathematics